Pulmonary thromboendarterectomy - YILDIZELİ, BEDRETTİN (TURKISH SOC CARDIOLOGY, 2010)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare disease characterized by the persistence of thromboemboli obstructing the pulmonary arteries as an organized tissue. The consequence is an increase in pulmonary vascular resistance resulting in pulmonary hypertension (PH) and progressive right heart failure. Pulmonary thromboendarterectomy (PTE) is the treatment of choice of chronic thromboembolic pulmonary disease. Pulmonary thromboendarterectomy is performed under hypothermia and total circulatory arrest. This procedure is associated with a low mortality rate in experienced centers and results in a dramatic improvement of hemodynamic parameters, functional status and survival rate. This surgery should be performed as early as possible in the history of this disease, preferentially before development of arteriolitis in the non obstructed territories. Because of the absence of clinically evident acute pulmonary embolism history in >50% of patients, the diagnosis of CTEPH can be difficult. Lung scintigraphic scan showing segmentary mismatched perfusion defects is the best diagnostic tool to detect CTEPH. Pulmonary angiography and high-resolution computerized tomography scan are required to establish the diagnosis and to assess the operability. A diagnostic right heart catheterization is required to confirm the diagnosis of PH and to determine the degree of hemodynamic impairment. If there is a good correlation between the pulmonary vascular resistance and the anatomical obstruction, pulmonary thromboendarterectomy should be proposed. Pulmonary or cardiopulmonary transplantation is indicated in this setting only when the lesions are too distal and thus inaccessible to endarterectomy. (Anadolu Kardiyol Derg 2010; 10: Suppl 2; 31-8)
Keywords: Pulmonary arterial hypertension; pulmonary embolism; pulmonary thromboendarterectomy; SURGICAL-TREATMENT; HYPERTENSION; ENDARTERECTOMY; ARTERY; VASCULOPATHY; VENTILATION; REGRESSION; EMBOLISM; OUTCOMES; DISEASE